2010
DOI: 10.3109/14015431003667652
|View full text |Cite
|
Sign up to set email alerts
|

Experimental flow study of modeled regular and irregular glottal closure types

Abstract: The present study shows the results of visualization experiments of the jet formation through a dynamic model of the human vocal folds. The model consists of two counter-rotating, 3D-shaped driven cams covered with a stretched silicone membrane. The 3D contours of the cams are a result of an optimized mapping of observed characteristic clinical vocal fold motions. The experiments are performed by using cams which produce the convex, triangular, rectangular, and concave or sand-glass regular glottis closure typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Optimization techniques were used to define cam geometries that yielded four different glottal closure types of interest (convex, concave, rectangular, and triangular). Kirmse et al [69] used different configurations of these cam geometries, including asymmetric driving functions, to explore the glottal jet in regular and pathological cases.…”
Section: Externally-driven Modelsmentioning
confidence: 99%
“…Optimization techniques were used to define cam geometries that yielded four different glottal closure types of interest (convex, concave, rectangular, and triangular). Kirmse et al [69] used different configurations of these cam geometries, including asymmetric driving functions, to explore the glottal jet in regular and pathological cases.…”
Section: Externally-driven Modelsmentioning
confidence: 99%
“…Besides excised larynges, synthetic vocal fold models with silicone vocal folds were carried out with the focus on the glottal insufficiency (Park and Mongeau, 2008;Kirmse et al, 2010;Kniesburges et al, 2013Kniesburges et al, , 2016. Pickup and Thomson (2009) and Zhang et al (2012) investigated asymmetric vocal fold oscillations with a silicone model.…”
Section: Introductionmentioning
confidence: 99%
“…Pickup and Thomson (2009) and Zhang et al (2012) investigated asymmetric vocal fold oscillations with a silicone model. Such models can mimic specific physiological and disordered motion patterns of the vocal folds for which they have been developed for and are therefore well-established in voice science (Zhang et al, 2004;Thomson et al, 2005;Park and Mongeau, 2008;Kirmse et al, 2010;Murray and Thomson, 2012;Kniesburges et al, 2013Kniesburges et al, , 2016Van Hirtum and Pelorson, 2017;Motie-Shirazi et al, 2019;Taylor et al, 2019;Romero et al, 2020). However, both ex vivo and synthetic larynx models are restricted regarding the spatial resolution of the measuring data of fluid flow, the vocal fold dynamics, and their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that the sound produced by the larynx is nonlinear [29] [31]- [34], which means that the phonation cycle loses its regularity when subglottic pressure is higher than the optimal phonation pressure [29]. The non-periodicity of speech cycles may be caused by the nonlinearity of the system assigned to the Coanda effect [30] [35]- [37], as well as to the presence of vortices in the glottic region [38]- [40] and in the supraglottic region [33] [38] [40]- [42]. Increased airflow increases these effects [36] [41]- [43].…”
Section: Discussionmentioning
confidence: 99%